Evolution of Rutherford's ion beam science to applied research activities at GNS Science. Issue 3 (2nd October 2021) - Kennedy, John V.; Trompetter, William Joseph; Murmu, Peter P.; Leveneur, Jerome; Gupta, Prasanth; Fiedler, Holger; Fang, Fang; Futter, John; Purcell, Chris
ABSTRACT: This manuscript outlines current research activities based on ion beam science at GNS Science in New Zealand. Ion beam analysis methods include Rutherford backscattering and nuclear reaction analysis which trace back to Rutherford's famous 'gold foil' and 'splitting the atom' experiments. These ion beam-based methods generally offer the ability to analyse materials for every element of the periodic table, to ppm concentrations, and with depth profiles ranging from a few nm to several microns. Ion beam methods are now also used to modify and create new materials precisely. Rutherford's early research now has a legacy at GNS Science's Materials team to discover, design, and develop materials for energy efficient modern applications for a low carbon future. These include magnetic sensors for security products, nanostructured magnetic materials for energy conversion, thermoelectric devices for energy harvesting, and catalytic development for clean energy carriers and energy efficient communication devices.